Intake of milk and range forage by nursing calves - A. Peischel; R.R. Schalles; Clenton E. Owensby; E.F. Smith (Kansas Agricultural Experiment Station Research Reports, 1980)
Adequate milk production by the cow to promote fast gain by her calf the first three months is important for heavy weaning weights. Calves consume considerable range forage by three months of age, and milk consumption begins to decrease. As grass begins to mature in September, milk from the dam and range forage eaten by the calf (as a percentage of body weight) decrease to below recommended protein level, so gains decrease. Weaning calves and placing them on a higher nutrition level in late August or early September may be considered when continued fast gains are desired.
Keywords: Cattlemen& #x27; s Day; 1980; Report of progress (Kansas State University. Agricultural Experiment Station); 377; Beef; Milk; Range forage; Nursing calves